Efficacy of Cylactin® (Enterococcus faecium NCIMB 10415) as a feed additive for pigs for fattening. (20th March 2018) - ,; Rychen, Guido; Aquilina, Gabriele; Azimonti, Giovanna; Bampidis, Vasileios; Bastos, Maria De Lourdes; Bories, Georges; Chesson, Andrew; Cocconcelli, Pier Sandro; Flachowsky, Gerhard; Gropp, Jürgen; Kolar, Boris; et al.
Abstract: Cylactin ® is the trade name for a feed additive based on dehydrated cells of Enterococcus faecium . It is marketed in three forms: Cylactin ® LBC ME10 and Cylactin ® LBC ME20 Plus – which contain the microencapsulated bacterium in concentrations of 1 × 10 10 CFU/g and 2 × 10 10 CFU/g, respectively – and Cylactin ® LBC G35, a granulated form with a guaranteed content of 3.5 × 10 10 CFU/g. In 2012, EFSA was requested by the European Commission to re‐evaluate the product when used as a zootechnical additive in feed for weaned piglets, sows and pigs for fattening. In the opinion delivered in 2015, the safety of the additive for consumers, users, the environment and target animals and its efficacy for piglets and sows were established. However, since only two efficacy studies with pigs for fattening could be considered and showed positive results, the Panel could not conclude on the efficacy for this target species due to insufficient data. The applicant has produced three additional feeding trials in pigs for fattening receiving the additive at the proposed inclusion level of 3.5 × 10 8 CFU/kg feedingstuffs, which are the subject of this assessment. None of these studies showed a significant effect on the performance of pigs for fattening. The data on average daily gain and feed to gain ratio of the three new studies and of the two from the previous opinion were pooled. Based on the results of this pooled analysis of five studies, but not supported by four out of the five individual studies, the EFSA Panel on Additives and Products or Substances used in Animal Feed concludes that Cylactin ® has some potential to improve performance of pigs for fattening at 3.5 × 10 8 CFU/kg feed.